2022
DOI: 10.1002/smll.202107145
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocally Photovoltaic Light‐Emitting Diode Based on Dispersive Perovskite Nanocrystal

Abstract: Integrating highly efficient photovoltaic (PV) function into light‐emitting diodes (LEDs) for multifunctional display is of great significance for compact low‐power electronics, but it remains challenging. Herein, it is demonstrated that solution engineered perovskite nanocrystals (PNCs, ≈100 nm) enable efficient electroluminescence (EL) and PV performance within a single device through tailoring the dispersity and interface. It delivers the maximum brightness of 490 W sr−1 m−2 at 2.7 V and 23.2% EL external q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The common strategy for the preparation of FAPbI 3 PeLED films is to add organic molecules to regulate the size and distribution of grain in the film to form island-like microcrystals. [4,6,8,14,[41][42][43][44][45][46][47][48] We select short-chain serine as an additive to optimize the perovskite film formation process for the control device. The optimal condition of the stoichiometric molar ratio in the precursor of serine: FAI: PbI 2 is 0.15:1.8:1 (Figure S10a,b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The common strategy for the preparation of FAPbI 3 PeLED films is to add organic molecules to regulate the size and distribution of grain in the film to form island-like microcrystals. [4,6,8,14,[41][42][43][44][45][46][47][48] We select short-chain serine as an additive to optimize the perovskite film formation process for the control device. The optimal condition of the stoichiometric molar ratio in the precursor of serine: FAI: PbI 2 is 0.15:1.8:1 (Figure S10a,b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Significant progress has been obtained with above 20% external quantum efficiency (EQE). [4][5][6][7] However, most of the PeLED have a serious EQE rolling-off under high current density. [8,9] Unlike QLEDs and low-dimensional PeLED, 3D PeLED does not restrict charge carriers, and its Auger recombination is not too severe to cause the EQE rolling off.…”
Section: Introductionmentioning
confidence: 99%
“…RP perovskites have been demonstrated to be an effective material system for LEDs and solar cells, including bifunctional applications of LED and solar cells. 64,93 A lower-energy photoluminescence is exhibited on the edge of exfoliated RP perovskites when n Z 3. 94 It has been demonstrated that the co-existence of the 3D structure and 2D/3D perovskite heterostructure are responsible for the lower-energy edge emission.…”
Section: Discussionmentioning
confidence: 99%
“…Metal halide perovskite nanocrystals (NCs) and quantum dots (QDs) have emerged as promising next-generation emitters for light-emitting diodes (LEDs) due to their unique properties, such as solution processability, near-unity photoluminescence quantum yields (PLQYs), emission wavelength tunability, and narrow emission spectra. The promising external quantum efficiencies (EQEs) of perovskite quantum dot light-emitting diodes (Pe-QLEDs) have been rapidly improved from 0.1% to more than 20% during the past few years. Although extensive efforts have been devoted to the development of perovskite QDs to realize high-performance devices, less attention has been paid to the charge transport layer (CTL) design for Pe-QLEDs. ,,, Charge transport materials (CTMs), both hole transport materials (HTMs) and electron transport materials (ETMs), play critical roles in Pe-QLEDs, including providing effective hole/electron injection/transport, blocking the electrons to avoid leakage, and making the LED devices more efficient and stable. The commonly used polymer HTMs in Pe-QLEDs, such as poly­[bis­(4-phenyl)­(2,4,6-trimethylphenyl)­amine (PTAA), poly­(4-butylphenyldiphenylamine) (poly-TPD), and poly­(9,9-dioctylfluorene-alt-N-(4-s-butylphenyl)-diphenylamine) (TFB), have presented good device performance due to their high hole mobility. The EQE of red and green Pe-QLEDs has been improved to 24.4% and 22.0% by employing Poly-TPD and PTAA as the hole transport layer (HTL), respectively. , However, most of these commercially available polymer HTMs are very expensive and suffer from production batch problems due to their complicated purification processes, which indicates great limitations for future mass production.…”
Section: Molecular Design Synthesis and Characterizationmentioning
confidence: 99%